2017
DOI: 10.1155/2017/4636809
|View full text |Cite
|
Sign up to set email alerts
|

Open Wedge High Tibial Osteotomy with Distal Tubercle Osteotomy Lessens Change in Patellar Position

Abstract: The purpose of this study was to investigate the change in patellar position after open wedge high tibial osteotomy (OWHTO) with distal tubercle osteotomy (DTO), comparing outcomes of conventional OWHTO in young adults with proximal tibia varus deformity but no arthritic manifestations. Thirty-three patients (mean age, 31.8 years) subjected to OWHTO/DTO were matched with 30 patients (mean age, 33.5 years) undergoing conventional OWHTO. Patellar position, as measured in pre- and postoperative standing lateral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
3
26
0
Order By: Relevance
“…For another reason, the change in tibial rotation after OWHTO may affect the LPT. 26 In our study, we also found that TT-TG distance showed a significant decrease after OWHTO. In our point of view, one possible explanation for this phenomenon is that the rotation of the distal tibia affects the TT-TG distance.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…For another reason, the change in tibial rotation after OWHTO may affect the LPT. 26 In our study, we also found that TT-TG distance showed a significant decrease after OWHTO. In our point of view, one possible explanation for this phenomenon is that the rotation of the distal tibia affects the TT-TG distance.…”
Section: Discussionsupporting
confidence: 72%
“…These researchers believed that BPI and CDI should not be relied upon in surgical procedures involving the proximal tibia, and they also noted that the MKI reflects a true reduction in patellar height because the measurement is based on femoral and not tibial reference. 23,26 We also did not observe a significant decrease in patellar height when using MKI for measurements. There was no change in patellar height following OWHTO using FPHI for measurements.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations